Novel A576T or M626I substitutions in the HAMP5 domain of histidine kinase FfOs1 alter ligand-binding pocket to mediate fludioxonil resistance in Fusarium falciforme - Bin Chen; Yuan Hu; Xuanming Zheng; Shanqinxue Gao; Jiawei Li; Aiguo Gu; Song Yang; Changyang Chen; Xiushi Song; Wenyong Shao; Changjun Chen (Pesticide Biochemistry and Physiology, 2026)

Cascade-activated DNA nano-gating coupled with P-doped Fe single-atom electrocatalyst for ultrasensitive dual-mode detection of circulating tumor DNA - Yanyi Long; Xiaofang Liu; Yong Zhang; Ruiming Zhang; Tao Gu; Ruixue Peng; Fei Deng; Xiaogang Luo; Changjun Hou; Danqun Huo (Chemical Engineering Journal, 2026)

Land cover change and its influencing factors in the Southeast Xizang Autonomous Region, China - Binghua Zhang; Linshan Liu; Yili Zhang; Bo Wei; Huxiao Qi; Dianqing Gong; Changjun Gu; Lanhui Li (Journal of Mountain Science, 2026)

The Effects of Poplar-Cyperus Esculentus Agroforestry System on Soil Nutrients and Microbial Communities in Northeast China - Wenxu Zhu; Weixi Zhang; Weiwei Gu; Xinyao Cong; Siqi Wu; Zhongyi Pang; Yanhui Peng; Jian Qiu; Zhuo sun; Changjun Ding (Journal of Soil Science and Plant Nutrition, 2026)

From AI modelling to validation: A 10-day pipeline for potential lead compounds validation - Bin Chen; Yuan Hu; Wen He; Guo Li; Ruiqi Liu; Jiawei Li; Xiujuan Li; Lingling Wei; Aiguo Gu; Song Yang; Changyang Chen; Xiushi Song; et al. (Pesticide Biochemistry and Physiology, 2026)

Satellite-based monitoring and hazard assessment of multiple flooding types in the Haihe river Basin induced by the July 2023 extreme rainstorm - Ziteng Xu; Wentao Yang; Xiya Zhang; Changjun Gu; Lingling Shen; Haibo Hu (Journal of Hydrology, 2025)

Triple binding pockets of AtSDH: Reduced affinity underpins SDHI- resistance in Alternaria tenuissima - Bin Chen; Ruiqi Liu; Wen He; Yuan Hu; JiaWei Li; Xiujuan Li; Aiguo Gu; Song Yang; Changyang Chen; Xiushi Song; Changjun Chen; Wenyong Shao (Pesticide Biochemistry and Physiology, 2025)

Target inhibition of rolling circle amplification generates G43 long nanowires for reverse signaling determination of alkaline phosphatase - Shuyu Zhu; Shiying Zhou; Liyuan Deng; Jiangbo Dong; Tao Gu; Xinyu He; Liang Jin; Changjun Hou; Danqun Huo (Analytica Chimica Acta, 2025)

Preliminary analysis of landslides induced by the 3 April 2024 Mw 7.4 Hualien, Taiwan earthquake - Yi Chen; Chuang Song; Zhenhong Li; Bo Chen; Chen Yu; Jyr-Ching Hu; Xingmin Cai; Shuang Zhu; Qianwen Wang; Yixin Ma; Changjun Gu; Suju Li; et al. (Landslides, 2025)

A new approach automatically calculating the outlet and upper catchment area of alpine glacial lakes - Yuhong Wu; Yong Nie; Farooq Ahmed; Changjun Gu; Wen Wang; Huayu Zhang; Qiyuan Lyu; Muchu Lesi; Sihui Zhang (Journal of Hydrology, 2025)

Hairpin probe-based one-pot multiplex isothermal amplification combined with bifunctional G-quadruplex (IHP-GT) for the detection of alkaline phosphatase - Shuyu Zhu; Shiying Zhou; Liyuan Deng; Tao Gu; Jiawei Li; Jian Chen; Xuemei Wang; Changjun Hou; Danqun Huo (Analytica Chimica Acta, 2024)

Computer vision-based real-time deflection monitoring of complex and sizeable steel structures - Yongqi Huang; Ruoqiang Feng; Changjun Zhong; Xiaoyu Tong; Xinxing Shao; Liuning Gu; Ze Hui (Engineering Structures, 2024)

Understanding the spatial heterogeneity of grazing pressure in the Three-River-Source Region on the Tibetan Plateau - Changjun Gu; Linshan Liu; Yili Zhang; Bo Wei; Bohao Cui; Dianqing Gong (Journal of Geographical Sciences, 2023)

Risk of plant invasions and management planning in the Tibetan Plateau, China - Bo Wei; Yili Zhang; Linshan Liu; Changjun Gu; Zhaofeng Wang; Haibin Yu; Bohao Cui; Dianqing Gong (Journal of Biogeography, 2023)
Aims Mountain environments have high biodiversity and face an accelerating plant invasion risk. Given the enormous ecological and economic value of these ecosystems, there is an urgent need to detect and rapidly respond to invasive species risk. Here, the Tibetan Plateau (TP) in China was selected to examine distribution patterns of invasive alien plants (IAPs) and propose management strategies. Location The Tibetan Plateau in China. Methods Based on native and non‐native occurrences of 123 IAPs alongside environmental variables, we assembled species distribution models and the MIGCLIM model to simulate suitable growth and dispersal areas under current climatic conditions. All IAPs were classified based on the predicted suitable area size, occurrence number and harm level to propose various management strategies. Results There was a significant separation between the climate niches of most IAPs and the climatic conditions of the TP, meaning the areas suitable for most IAPs were limited to low latitudes and elevations. These areas also have further dispersal risks and risks for new IAPs being introduced. Among 123 IAPs, 23 species had above‐average occurrences and suitable distribution areas; in the remaining 100 occurrences and distributions, at least one IAP was less than the average. Main Conclusions Suitable areas for IAPs in the TP are currently limited to low‐elevation regions, which are also at a higher risk of further expansion. Management measures should focus on potential high‐risk areas and diffusion pathways where IAPs can spread further. Efforts should prevent species that have not been established but have large potential suitable areas from being introduced, eradicate established IAPs with limited suitable areas, and control established IAPs. These results can provide a reference for developing more efficient and cost‐effective management strategies.

Reduction of miR-133a-3p contributes to apoptosis and gasdermin E-mediated pyroptosis of keratinocytes in skin exposed to ultraviolet B radiation - Changjun Song; Wenlan Zhang; Ta Xiao; Min Li; Yiqun Zhang; Xuecui Wei; Yujie Chen; Ni Lian; Yangying Ke; Hui Yu; Min Li; Heng Gu; et al. (Journal of Photochemistry and Photobiology B: Biology, 2023)